Morphophysiological changes in seedlings of two wood species after application of salicylic acid - Lima Rocha, Maria Eunice; Barbosa de Souza, Fernanda Ludmyla; Fortado vera Cruz, Maria Soraia; Ribeiro Coutinho, Pablo Wenderson; de Matos Malavasi, Marlene; Contro Malavasi, Ubirajara (Revista Ceres, 2022)
The forestry production sector uses several strategies to minimize post-planting seedling losses. Some practices can modulate characteristics of interest for plant growth and defense, including changes in the light exposure, reduced watering, fertilization, and chemical or mechanical stimulus. This work quantified morphophysiological changes on Schinus terebinthifolius and Cedrela fissilis seedlings resulting from the application of salicylic acid for eight weeks. The experimental design was completely randomized, composed of four treatments (0, 100, 200, and 300 mg L-1 of salicylic acid). The quantified variables included height, diameter, and dry matter mass of the root and aerial parts. Additionally, leaf area, root-cell electrolyte loss, lignin content in roots, and stem plus phenolic compounds were quantified. On aroeira seedlings, the height, aerial, and radicular dry matter masses and leaf area were reduced while the diameter and the lignin content increased directly as a function of salicylic acid doses. In cedro seedlings the dose of 100 mg L-1, however, resulted in a better balance of plant biomass and would, therefore, be the most indicated dose for the species. The application of salicylic acid for 8 weeks on seedlings of both species resulted in the most relevant morphophysiological modifications correlated with quality characteristics of seedlings of woody species.